Secondary Flow and Endwall Optimization of a Transonic Turbine - Abdul Rehman; Bo Liu; Muhammad Afzaal Asghar (Energies, 2019)
A detailed numerical analysis of secondary flows in a transonic turbine is presented in this paper. The turbine stage is optimized by mitigating secondary flow through the method of non-axisymmetric endwall design. An automated optimization platform of NUMECA/Design3D was coupled with Euranus as a flow solver for the numerical investigation. The contoured endwalls of the stator and the rotor hub were designed based on equidistant Bézier curves along the camber line in the blade channel. The initial design samples were ten times the number of the design variables, and were generated through the LHS method for database generation. The optimization of the endwalls was achieved by using a state-of-the-art multi-objective optimization algorithm, NSGA-II, connected with the BPNN to increase the isentropic efficiency and decrease the secondary kinetic energy, while the mass flow and the degree of reaction were constrained to remain on the datum value as in the original geometry. The individual optimization of the hub endwalls of the stator and the rotor produced an increase in the efficiency of 0.27% and 0.25%, respectively, resulting in a cumulative improvement of 0.46% in the efficiency. The increase in the performance was analyzed at part-load conditions, and it was further confirmed through unsteady simulations.